Anxiolytic effect of an extract of Salvia miltiorrhiza Bunge (Danshen) in mice. (10th January 2021) - Lin, Yu-Shih; Peng, Wen-Huang; Shih, Mei-Fen; Cherng, Jong-Yuh
Abstract: Ethnopharmacological relevance: Salvia miltiorrhiza Bunge (Danshen), a traditional Chinese medicine, has demonstrated in modern studies for its pharmacological activities in treatments of CNS disorders like insomnia, dysphoria. However, its application on anxiolytic effect from the ethanol extract of Salvia miltiorrhiza Bunge (SMEtOH ) has not yet been reported. Materials and methods: This study investigated the anxiolytic effect of the SMEtOH using the elevated plus-maze test (EPM) and the hole-board test (HBT) with diazepam and buspirone as positive controls. Also, the spontaneous locomotor activity of mice had been investigated in the open field. Further, we have illustrated the anxiolytic mechanisms of SMEtOH with its influencing upon GABAergic and/or serotonergic nervous systems via a method that SMEtOH was co-administered with flumazenil, a benzodiazepine (BZD) antagonist, or a drug (WAY-100635), a selective 5HT1A receptor antagonist. Results: In hole-board test, results presented that SMEtOH increased head-dip counts and duration time. On the other hand, a decrease in spontaneous locomotor activity was observed. In the EPM test, SMEtOH increased the percentage of open-arm entries and the percentage of time spent in open arms. However, when SMEtOH co-administered with flumazenil or WAY-100635, the anxiolytic effect of SMEtOH was significantly counteracted. Conclusion: From these results, we can conclude that the anxiolytic mechanism of SMEtOH is exerted through an activation of the BZD and 5HT1A receptors.